1993
DOI: 10.1111/j.1365-2044.1993.tb07427.x
|View full text |Cite
|
Sign up to set email alerts
|

The performance of two intensive care humidifiers at high gas flows

Abstract: SummaryHigh continuousflow breathing systems are now available to provide fresh gasflows well in excess of 100 I.min-I in continuous positive airway pressure systems used for respiratory support. The performance of two commonly used intensive care humidifiers. the Kendal Conchatherm and the Fisher and Paykel FP310 have been assessed a t j o w s of 50, 75, 100, I25 and 150 I.min-'. Their performance when using two humidifiers connected in parallel and in series was also studied. A t a fresh gasflow of 100 I.min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Humidi®cation can be provided during CPAP application. HARRISON et al [77] suggested that two vapour humidi®ers in series need to be added to provide effective humidi®cation at high gas¯ows. There are no published clinical trials which compare outcomes of application of CPAP with and without humidi®cation.…”
Section: Equipmentmentioning
confidence: 99%
“…Humidi®cation can be provided during CPAP application. HARRISON et al [77] suggested that two vapour humidi®ers in series need to be added to provide effective humidi®cation at high gas¯ows. There are no published clinical trials which compare outcomes of application of CPAP with and without humidi®cation.…”
Section: Equipmentmentioning
confidence: 99%